PENGARUH STRATEGI MANAJEMEN PERUBAHAN DAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MERUBAH BUDAYA ORGANISASI - Sunasih Mulianingsih (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
Organizational culture is one of several situational moderators that are crucial in evaluating leadership effectiveness. Furthermore, these ideas reflect all the elements that "keep" the members of the organization together. Leaders must have a vision and mission as well as a clear understanding of the strategic objectives of the organization in order to encourage change. Research aims to provide exposure to the effects of change management and transformational leadership in the culture of an organization. This study uses a qualitative approach with exploratory methods to set priorities, develop definitions and determine the final research design. The results of this study will provide an overview of the importance of a change in organizational culture through transformational leadership and change management strategies so that an organization or company can survive and improve its performance.